2016
DOI: 10.1080/16066359.2016.1212338
|View full text |Cite
|
Sign up to set email alerts
|

The experience of gambling problems in British professional footballers: a preliminary qualitative study

Abstract: Football, gambling and gambling-harms v3; 1 st July 2016 2 Media reports suggest high rates of gambling amongst professional footballers but little is known about how footballers develop and then seek help for gambling problems. Here, we report the findings of in-depth, qualitative interviews with 11 British professional footballers who had, or who were, being treated for gambling problems at a residential clinic. These individuals experienced gambling as a highly salient feature of life as a professional foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…Participant C5 suggested that '...they don't like to er, admit depression with the club doctors because obviously they fear for their career'. This supports the findings ofLim et al, (2017), and suggests that depression may be under-reported and a larger injury estimates were as high as 100%, '...I think they've probably all been injured in some way or another...' (C4). This supports the evidence that injury in football is common(Hawkins & Fuller,…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Participant C5 suggested that '...they don't like to er, admit depression with the club doctors because obviously they fear for their career'. This supports the findings ofLim et al, (2017), and suggests that depression may be under-reported and a larger injury estimates were as high as 100%, '...I think they've probably all been injured in some way or another...' (C4). This supports the evidence that injury in football is common(Hawkins & Fuller,…”
supporting
confidence: 68%
“…Recent UK research has found that gambling is a common part of life as a professional footballer (Lim et al, 2017). Findings have suggested that British professional footballers previously treated or currently being treated for this addiction often began gambling as young players amongst friends but it became problematic when continued by the player in isolation (Lim et al, 2017). Emotional challenges such as a decline in performance, contract releases, or injury increases the risk of problematic gambling.…”
Section: Addiction and Substance Misusementioning
confidence: 99%
See 1 more Smart Citation
“…If the prevalence of problem gambling in the sport environment is elevated relative to that in the general population, the question arises as to what factors in that environment contribute to the problem. In football, problem gambling has been associated with factors such as gambling as part of the social networks of young players, high salaries, spare time, gambling as a shared leisure pursuit, and the competitive and emotional challenges of the game (Lim et al, 2016). Wardle and Gibbons (2014) reported that 25% of respondents thought they were encouraged to gamble by teammates and 31% that they were encouraged by gambling companies.…”
Section: Gambling and Alcohol Consumption Among Athletesmentioning
confidence: 99%
“…All of these factors may help to identify occupational groups that could be more likely to gamble (i.e. occupational sectors with high incomes, attracting men or relative youth 14) ). Indeed, key drivers of gambling include social influences, which comprise influence (either negative or positive) from colleagues at the workplace 15,16) .…”
Section: Introductionmentioning
confidence: 99%